Application of Puzzle Learning Media for Elementary School Children in Science Learning on the Metamorphosis of Frogs - Jesicha Nais; Nurmaelinda; Tina Sholikha; Rina Almaidah; Prety Nurfadhilah (Mazidah: Journal Of Educational Research, 2025)
Science (IPA) is a crucial subject in elementary schools, encompassing natural phenomena, thinking, and problem-solving. However, students often find science difficult, abstract, and irrelevant, primarily due to unengaging teaching methods and a lack of interactive media. Recognizing this challenge, an educational initiative in Temiyang Village, Kroya District, implemented the "Biokids Hassle-Free Frog Metamorphosis Tutoring Program with Children in the Temiyang Village Environment." This program aims to increase elementary school students' understanding and interest in frog metamorphosis through the use of innovative learning media. The approach includes the use of educational videos, animations, images, and the creation of puzzles depicting the frog metamorphosis cycle from drawing paper and Styrofoam board. It also encourages group problem-solving. It is hoped that this media implementation will help students understand biology concepts more easily and enjoyably, and motivate their active participation in learning.